Ammonia/amine electronic gas sensors based on hybrid polyaniline–TiO2 nanocomposites. The effects of titania and the surface active doping acid. Issue 26 (22nd March 2015) - Mikhaylov, S.; Ogurtsov, N.; Noskov, Yu.; Redon, N.; Coddeville, P.; Wojkiewicz, J.-L.; Pud, A.
<x xml:space="preserve">Abstract</x> Morphology and sensor responses.